THE DESIGN OF TOOLS AND LOCATION DETERMINATION FOR THE VISUALLY IMPAIRED USES A MICROCONTROLLER-BASED ULTRASONIC SENSOR - Mulkan Iskandar Nasution; Syahrul Ardiansyah (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2020)
....